Defective responsiveness to ascorbic acid of neutrophil random and chemotactic migration in Felty's syndrome and systemic lupus erythematosus. - Goetzl, E J (1976)
Polymorphonuclear (PMN) leucocytes from 4 patients with untreated systemic lupus erythematosus (SLE) showed defective random migration (P less than 0-05) and depressed chemotactic responses to C5a and kallikrein (P less than 0-01) compared to PMN leucocytes from normal subjects, or patients with rheumatoid arthritis (4) or Felty's syndrome (4) when examined at a standardized cell concentration with a micropore filter radioassay but not with a conventional Boyden technique. Normal in vitro enhancement of PMN leucocyte random and chemotactic migration by sodium ascorbate was absent in SLE and Felty's syndrome, but sodium ascorbate gave normal stimulation of hexose monophosphate shunt activity in the PMN leucocytes precluding a defect in ascorbate transport.